STYLOMETRY: STATISTICAL APPROACH INTO FILM STYLE - Patawari, Muhammad Yunus (Capture : Jurnal Seni Media Rekam, 2019)
So far the study of cinema is still dominated by the use of a Narrative Analysis approach, where its weaknesses do not have empirical evidences, so the resulting analysis is assumptions which then followed by a text debate. Statistical Style Analysis or Stylometry is an alternative method in the study of cinema used to measure the director's formal (film style) parameters. This study applied Stylometry to the films by Chaerul Umam for decades (1970-2000). From this study it was found statistically that the Chaerul Umam style film underwent a change in the use of zoom techniques, the dominance of the use of medium shot (MS) and classified as small ASL units under 9 seconds / shot which is 6.6 / seconds.